Transcriptome Reveals Multi Pigmentation Genes Affecting Dorsoventral Pattern in Avian Body - Xi, Yang (Front Cell Dev Biol, 2020)
Certain animals exhibit a special dorsoventral pattern with a lighter ventral side compared to the dorsal one and this phenomenon was preserved in the long-term evolution process. Birds also retain this trait. Recently, Inaba et al. (2019) found that ASIP (agouti signal protein) regulated interconversion between different melanocyte types leads to dorsal stripe pattern, which may partly explain the birds’ dorsoventral plumage color difference. In this study, we used the embryo samples of LBM (light brown mottling) ducks (Anas platyrhynchos) with white ventral and dark dorsal body parts to investigate the mechanism of dorsoventral color variation. Firstly, melanin deposition process of duck embryos was investigated. The result indicated that E13 and E16 were the active stages of melanin synthesis. Moreover, the melanin deposition on the dorsum of LBM ducks was higher than that on the ventral side throughout. Then, RNA-seq was conducted for the dorsal and ventral skin tissues from E7 (early), E13 (middle) and E19 (late) of LBM ducks. Expression pattern analysis showed that the mRNA expression of most melanin synthesis related genes were at the highest level at E13, which was consistent with the section analysis. A correlation was found between melanogenesis pathway and dorsoventral color difference by co-expression analysis. In the DEG (differentially expressed gene) analysis, we added the dorsal skin transcriptome of embryonic white and black duck of same subspecies (Anas platyrhynchos domestica) for horizontal comparison. The results showed that 8 melanogenesis related genes (TYR, TYRP1, MLANA, RAB38, OCA2, TSPAN10, MC1R, and MSLN) were the common DEGs (Differential expressed genes) in the comparisons of body parts and breeds suggesting that the underlying molecular regulatory mechanism of dorsoventral plumage color difference may be similar to that of albino and melanic duck, which were caused by the different expression of multiple genes in melanin synthesis pathway. In addition, the molecular regulation of melanin synthesis pathway in the dorsal and ventral side of LBM ducks was analyzed. In this pathway, ASIP, MC1R, TYR, and TYRP1 have differential mRNA expression. ASIP, as an upstream gene in this pathway, was likely to play a decisive role in determining the dorsoventral plumage pattern.